Jaru dictionary. - Wrigley, Matthew; Kimberley Language Resource Centre (Halls Creek, W.A. : Kimberley Language Resource Centre, 1992)
Jaru-English dictionary with English-Jaru finder list ; provides an English definition of the Jaru word and information on its source ; some entries include an illustrative sentence and its translation and references to words with a similar meaning; word lists.
"A Kimberley Language Resource Centre Project" -- Cover.
Produced by Matthew Wrigley.
Keywords: Aboriginal Australians -- Western Australia -- Kimberley -- Languages -- Dictionaries; Djaru language -- Dictionaries; Language - Vocabulary - Dictionaries and glossaries; Jaru / Djaru language (K12) (WA SE 52-10); Jaru language K12.; Kimberley area (WA SD51, SD52, SE51, SE52)